Decline in the contribution of microbial residues to soil organic carbon along a subtropical elevation gradient - Yang, Liuming; Lyu, Maokui; Li, Xiaojie; Xiong, Xiaoling; Lin, Weisheng; Yang, Yusheng; Xie, Jinsheng (The Science of the total environment, 2020)
There has been an increasing interest in studying microbial necromasses and their contribution to soil organic carbon (SOC) accumulation. However, it remains unclear how the interaction among climate, plants, and soil influence the microbial anabolism and how microbial necromass contribute to SOC formation. Here, we assessed the relative contribution of microbial residues to SOC pool across a subtropical elevation gradient (ranged from 630 to 2130 m a.s.l.) representing a subtropical ecosystem on Wuyi Mountain in China, by using amino sugars as tracers. Analysis of topsoil (0–10 cm) amino sugars and the composition of microbial community across this gradient revealed that the soil total amino sugars accounting for 12.2–25.7% of the SOC pool, decreased with increasing elevation. Moreover, the linear reduction in the bacterial-derived carbon (C) and an increase in the ratio of fungal- to bacterial-derived C with increasing elevation suggested the reduction in the contribution of bacterial-derived C to SOC pool across this elevation gradient. The divergent changes in the contribution of the microbial residues to SOC infer a potential change in SOC composition and stability. The microbial-derived SOC formation and its climatic responses are influenced by the interaction of vegetation types and soil properties, with soil amorphous Fe being the determiner of soil amino sugar accrual. Our work highlights the importance of understanding ecosystem type and mineral composition in regulating microbial-mediated SOC formation and accumulation in responses to climate change in subtropical ecosystems. [Display omitted] •Soil amino sugars were measured along a subtropical elevation gradient.•The microbial residues related to SOC reduced with increasing elevation.•Soil mineral protection impaired the microbial necromass formation in soils.•Fungal-derived carbon contributed more to SOC than the bacterial-derived carbon.